Cross layer weight based on demand routing protocol for mobile ad hoc networks. (2016) - Gulati, Mandeep Kaur; Kumar, Krishan
Due to the mobility and limited energy of the mobile nodes, frequent link failures occur in mobile ad hoc network (MANET) which makes quality of service (QoS) routing a challenging task. In this paper, we consider these issues and propose a cross layer weight based on demand routing protocol (CLWORP) which uses the weight-based route strategy to select a stable and energy efficient route in order to enhance quality of service performance. The weight of a route is decided by three factors: link signal strength, residual energy and drain rate. Multiple routes are discovered from the source node to the destination node with the different weight values. Then the path with the largest weight value is selected at the destination. Simulation results show that the proposed CLWORP outperforms AODV especially in a high mobility environment.